2022
DOI: 10.1088/1755-1315/1018/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Geographic Indications to Maintain The Quality of Robusta Coffee on The Slopes of MT. Arjuna, Welirang, and Bromo

Abstract: Robusta coffee is grown on Mount Arjuna, Welirang, and Bromo in East Java can get legal protection as a geographical indication. This study analyzes the need for Robusta coffee to get legal protection as a Geographical Indication to maintain coffee quality. This study employs qualitative approaches, including interviews, observations, and documentation. The researchers selected these respondents according to the categories studied and had coffee plantations on Mount Arjuna, Welirang, and Bromo. The research sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on the conversation and interviews, it appears that each office is delegating responsibility to other parties. The provincial Estate and Crop Bureau indicated that it should be the responsibility of the district administration, however the districts believe that the provincial government does not help enough to develop Gis (14). And, in the end, the offices will face the usual dilemma of who will support the GIs as it is costly to register and maintain.…”
Section: ) Robusta Coffee Gi's Challenge: Disproportionality Of Produ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the conversation and interviews, it appears that each office is delegating responsibility to other parties. The provincial Estate and Crop Bureau indicated that it should be the responsibility of the district administration, however the districts believe that the provincial government does not help enough to develop Gis (14). And, in the end, the offices will face the usual dilemma of who will support the GIs as it is costly to register and maintain.…”
Section: ) Robusta Coffee Gi's Challenge: Disproportionality Of Produ...mentioning
confidence: 99%
“…To demonstrate how complex the addressed issue, the GIs in Lampung Province are administered by the following offices: The issue is that a lack of coordination generates other challenges, such as limited budgets, difficulty in developing requirement books, and one door standardizedmarketing. West Lampung Regency has a particular initiative to promote Robusta Lampung Coffee, however the other two regions in the Regional Autonomy, such as Tanggamus and Way Kanan, do not [14]. However, even when the local government begins to make attempts to create GIs, it encounters additional challenges, including a shortage of budget resources.…”
Section: ) Robusta Coffee Gi's Challenge: Disproportionality Of Produ...mentioning
confidence: 99%